Causes and risk factors associated with pre-weaning lamb mortality in Colima, Mexico - García-Pérez, Miguel (2021)
The study evaluated the causes and risk factors associated with pre-weaning mortality in extensive and semi-extensive lamb production systems in a municipality in the coastal region of the state of Colima, Mexico. Mortality was assessed by necropsy and information on the number of births and the body condition of the ewe before lambing, litter size, sex, breed and weight of the lamb was recorded at the time of lambing. Statistical analysis was done using the Chi-square test of independence and by means of stepwise Logistic Regression. The overall pre-weaning mortality rate was 27.9%. The number of lambs born and dead was 875 and 244, respectively, where 88.1% of the mortality occurred during the first 48 hours of birth due to starvation-exposure syndrome. Pre-weaning mortality was significantly associated (p<0.05) with the flock, body condition of the ewe at parturition and with the lamb´s weight at birth and breed. Lambs that weighed less than 2 kg at birth were eight times more likely to die than heavier lambs (OR = 8.30) and lambs born to ewes with a body condition of less than two at lambing were more likely to die than those born of a sheep with higher body condition (OR = 3.02).